Information about management of chronic drug therapies prescribed at hospital discharge: does it affect patients' knowledge and self-confidence? - Claudia Pileggi; Emilia Caligiuri; Carmelo G. A. Nobile; Maria Pavia (BMC, 2018)
Abstract Background Hospital stay represents the opportunity for a change of therapy, about which patients may not know indications, contraindications, and mode of administration, which may lead to dosing errors, drug interactions, side effects, etc. It is therefore vital to communicate appropriate information to the discharged patient with a new prescription drug. The purpose of the study was to evaluate: 1) how communication about new chronic therapies is managed at hospital discharge and what kind of information is provided to patients; 2) to what extent patients are aware and confident in the management of these medications; 3) whether the way communication is provided affects patients' awareness and self-confidence in the management of these therapies. Methods Participants were adult patients who were prescribed at least one new chronic medication at hospital discharge. A telephone interview after hospital discharge was performed to assess whether or not hospital healthcare personnel had given information about prescribed therapies and which aspects of therapies had been object of information. Results Five hundred thirty patients were interviewed. 67.7% reported having received counseling by the hospital physician, while 32.3% by discharge form. Basic information on treatment was provided to the great majority of patients, whereas only few patients reported to have been informed about eventual side effects and related behavior in case of side effects. Conclusions Several aspects of patients' knowledge and self-confidence on long term medications prescribed at hospital discharge need to be improved and the way communication is provided has a crucial role in the empowerment of patients in the management of these medications.